2005
DOI: 10.5688/aj690591
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Education and Research at the University of Pittsburgh (GEAR-UP): A Program to Educate Students about Pharmaceutical Research

Abstract: Objectives. To develop a program to inform and encourage students enrolled in pharmacy and related programs in the United States about research careers in the pharmaceutical sciences. Design. The Graduate Education and Research at the University of Pittsburgh (GEAR-UP) Program was designed with 2 components: a mini-graduate school and a summer internship. The mini-graduate school provided information about research. Summer internships provided intensive peer-learning research experiences. Outcomes. Since 2002,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6] However, much of this literature stresses the need to foster research skills and student pharmacist interest in research. [7][8][9][10] Mentoring is believed to be 1 method of increasing research interest among student pharmacists. The Accreditation Council for Pharmacy Education (ACPE) Guideline 23.4 states, "Colleges and schools should implement strategies and programs to broaden the professional horizons of students in areas such as scientific inquiry, scholarly concern for the profession, [and] the relevance and value of research."…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, much of this literature stresses the need to foster research skills and student pharmacist interest in research. [7][8][9][10] Mentoring is believed to be 1 method of increasing research interest among student pharmacists. The Accreditation Council for Pharmacy Education (ACPE) Guideline 23.4 states, "Colleges and schools should implement strategies and programs to broaden the professional horizons of students in areas such as scientific inquiry, scholarly concern for the profession, [and] the relevance and value of research."…”
Section: Introductionmentioning
confidence: 99%
“…3 The CSA program coupled with recruiting efforts, such as the Graduate Education and Research at the University of Pittsburgh (GEAR-UP) program, 2 have provided a multifaceted approach to recruiting and supporting clinical pharmaceutical sciences students, and has appropriately begun to increase students' interest in this program. Schools of pharmacy can partner with hospitals to implement the CSA program in order to fulfill the recommendation by the Commission on the Future of Graduate Education in the Pharmaceutical Sciences to increase the number of graduate students in pharmaceutical sciences graduate programs.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent survey of schools and colleges of pharmacy demonstrated that the number of clinical pharmaceutical scientist PharmD/PhD programs is rapidly increasing nationally with 16 existing programs and 10 programs currently in planning. 3 Each institution that offers or is planning to offer a clinical scientist PhD program is faced with the issue of development of students' clinical pharmacy skills as a component of the training, as well as identifying mechanisms to support students.…”
Section: Introductionmentioning
confidence: 99%
“…5 Research courses as PharmD electives, on the other hand, were found to be more palatable to the student. [6][7][8] While the average PharmD student may not recognize the value of a curricular research option, PharmD graduates do appear to view research experience as a priority. [9][10][11] Of over 400 University of Michigan PharmD graduate survey respondents, 82% stated that the required research project should be continued, and that exposure to research translated into job market flexibility and adaptability, increased job satisfaction, and increased career achievement.…”
Section: Introductionmentioning
confidence: 99%